Change in Corneal Astigmatism After Phacoemulsification with Rigid Intraocular Lens Implantation : Change in Corneal Astigmatism After Phacoemulsification - Jahangir, Sana; Ali, Muhammad Hassaan; Hamza, Uzma (Pakistan Journal of Health Sciences, 2024)
Phacoemulsification with lens implant is the preferred method of cataract extraction nowadays. In resource-deficient settings, rigid polymethyl methacrylate (PMMA) lenses are implanted which require enlargement of corneal incision to 5.5mm. Objectives: We conducted this study to evaluate the effect of corneal incisions secured with a single suture on corneal astigmatism after routine cataract surgery. Methods: It was a quasi-experimental study conducted at tertiary care hospitals. Sixty patients were studied and preoperative visual acuity and keratometry readings were noted. After standard phacoemulsification, a 5.5mm rigid PMMA lens was implanted in the bag, and the corneal incision was sutured using a single central 10/0 nylon suture. Visual acuity and keratometry readings were noted on 1st postoperative day, 1-week postoperatively, and 6-weeks postoperatively and compared with pre-operative values. Results: The mean age was 59.27 ± 10.72 (range: 46 – 78) years. There were 32 (53.3%) males and 28(46.7%) females in the study. The mean preoperative keratometry reading was 0.89 ± 0.70 D, and the mean first-day postoperative cylinder was 1.94 ± 0.98 D (p < 0.05). The mean astigmatism at the 6th week postoperatively was 0.96 ± 0.65 D, and its comparison with the pre-operative astigmatism was statistically not significant (p > 0.05). Surgically induced astigmatism was found to be 0.07 diopters. Almost 60% of the patients achieved uncorrected 6/7.5 or better visual acuity, and more than one-third of patients achieved 6/6 best corrected visual acuity six weeks after the cataract surgery using the described technique. Conclusions: Phacoemulsification with 5.5mm PMMA IOL with a central single suture is an effective procedure for postoperative astigmatism and visual outcome.